Belief or Disbelief? Unraveling the Meaning of the Use of Quranic Verses as Amulets in Indonesian Muslim Society - Samsudin, Izal (Islamic Religious Education Departement, 2026)
The practice of using Quranic verses as amulets among Indonesian Muslims indicates complex issues related to religious understanding and the concept of monotheism. This study aims to examine this phenomenon and its implications. Using qualitative methods, data were collected through a literature review and field observations, and then analyzed from an Islamic theological perspective, specifically the concept of monotheism and the views of Islamic scholars. The results indicate that this practice persists, influenced by local traditions and mystical beliefs, and fueled by limited understanding. While some view it as a spiritual endeavor, Islamic scholarship warns that believing Quranic verses have independent power can deviate from the creed. The study recommends strengthening the understanding of the creed through more effective Islamic da'wah and education.